Recent advances of starch-based excipients used in extended-release tablets: a review. (2nd January 2016) - Hong, Yan; Liu, Guodong; Gu, Zhengbiao
Abstract: In recent years, polysaccharides, including starch and its derivatives, have been widely used in the pharmaceutical industry, including as diluents, fillers, binders, disintegrants and glidants. The use of native starch as excipient in extended-release tablets is limited due to its low compactibility and enzymatic degradability, leading to the formation of weakly structured tablets. To overcome these limitations and expand the application of starch as an excipient, researchers have modified starch by physical and chemical methods, as well as by enzymatic hydrolysis. Some starch derivatives, including retrograded starch, pregelatinized starch, carboxymethyl starch, starch acetate, cross-linked starch and grafted starch have recently been introduced as excipients in oral tablets to control drug release. In this review, applications of starch and its derivatives as extended release excipients are reviewed and future frontiers are described.